2020
DOI: 10.2478/slgr-2020-0036
|View full text |Cite
|
Sign up to set email alerts
|

Is Cluster Analysis the Appropriate Statistical Method for Planning the Optimal Locations for Automated External Defibrillators?

Abstract: The Automated External Defibrillator (AED) is an intuitive device used by witnesses of an incident without medical training in cases of sudden cardiac arrest. Its operation consists in delivering an electrical pulse to the cardiac conduction system, as a result of which normal heart rate is restored. The lack of awareness in society concerning the usefulness of the device and the inadequate deployment of AEDs result in their too infrequent application by witnesses of incidents. The aim of this paper is to veri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…It was found that the length of time to reach the patient is less than eight minutes, which is the standard assigned to the emergency medical unit to reach out-of-hospital cardiac arrest patients to increase the chance of survival. 22,24,27 The study also found that almost all areas that reach emergency patients do not have AED equipment installed in public places, which corresponds to the nature of residence. Most of them live in one house or in an allotted village, which is far from the areas where an AED is located, such as a bus station or shopping mall.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…It was found that the length of time to reach the patient is less than eight minutes, which is the standard assigned to the emergency medical unit to reach out-of-hospital cardiac arrest patients to increase the chance of survival. 22,24,27 The study also found that almost all areas that reach emergency patients do not have AED equipment installed in public places, which corresponds to the nature of residence. Most of them live in one house or in an allotted village, which is far from the areas where an AED is located, such as a bus station or shopping mall.…”
Section: Discussionmentioning
confidence: 91%
“…Currently, AEDs in Thailand have been prescribed to be installed in public areas such as bus stations and shopping malls, but it has been found that there are still very few compared to the proportion of the area, which may be due to the high price of the device, approximately three thousand US dollars per device. 21,22 Although there is a law in Thailand that requires an AED device to be available to be used in first aid. That means the general public can use this tool when seeing a patient undergoing an out-of-hospital cardiac arrest.…”
Section: Introductionmentioning
confidence: 99%